EVALUASI PENGELOLAAN KAS DAN STRATEGI PROMOSI PADA UMKM BAKMIE DI KECAMATAN SENTOLO, KABUPATEN KULON PROGO - Siwi Pratiwi; Nugraeni Nugraeni (Bajang Institute, 2026)
Micro, Small, and Medium Enterprises (MSMEs), particularly small-scale culinary businesses, still frequently experience problems with financial management and digital media utilization. This community service activity was conducted from May 1–15, 2026, at the Bakmie & Nasi Goreng Pak Wignyo MSME, located in Pasar Lama Sentolo, Kulon Progo Regency. The activity aimed to assist business owners in simple daily cash recording and enhance business promotion through the use of Google Maps. The methods used in this activity included initial observation, direct mentoring, and activity evaluation. The results showed that business owners began to be able to record income and expenses more regularly using a simple cash flow format provided. Furthermore, the business was successfully registered on Google Maps, making business information more easily found by consumers. Based on the evaluation, the direct mentoring activities helped business owners understand financial management and digital promotion more easily. This activity is expected to serve as an example of simple mentoring that can be applied to other culinary MSMEs.